Pengelolaan Sarana dan Prasarana dalam Meningkatkan Mutu Pendidikan di MAN 1 Mojokerto: Management of Facilities and Infrastructure in Improving the Quality of Education at MAN 1 Mojokerto - Basith, Abdul (ISEDU : Islamic Education Journal, 2023)
There is an equal right between private and public schools to receive non-physical allocation funds, namely BOS funds. One of the BOS funds is intended for the cost of managing facilities and infrastructure such as the cost of minor repairs, rehabilitation and purchasing equipment that is not too expensive. The problem in this study is that not all educational institutions, both private and public, have the ability to manage their educational facilities and infrastructure. So that many infrastructure facilities that were initially lightly damaged are left to be severely damaged. This research is a field research that uses a qualitative approach. The research subjects in this study were the Head of Madrasarah, Waka Sarana Prasarana and Waka Kurikulum. Based on the results of research and discussion, it can be concluded in several things: first, MAN 1 Mojokerto succeeded in planning infrastructure facilities in accordance with the indicators that researchers appear, namely the needs, financing and prioritization of the three indicators MAN 1 Mojokerto made a strategic plan MAN 1 Mojokerto in improving the quality of education. Second, the procurement of infrastructure facilities in improving the quality of education MAN 1 Mojokerto has set the procurement of infrastructure facilities by means of maintenance, purchase and maintenance in accordance with the strategic plan and standards in place. Procurement of infrastructure facilities in improving quality at MAN 1 Mojokerto is in accordance with the indicators that researchers have come up with, namely determination, procurement sources and quality.